Pontes entre a literatura e o ensino de história : o romance Shaira e a saudade - Simões, Jussara Correia da Silva (2022)
The present work has the general objective of analysing literature as a possibility for the teaching of History. To achieve this end, we used didactic sequences in work with the novel “Shaira e a saudade” in the 2nd grade of High School at Colégio Estadual Santa Cruz, located in Monte Santo, semi-arid region of Bahia. The specific objectives are to problematize my memories as a teacher and the relation they have with my teaching practice and the writing of novels; to relate the literary narrative with the historical one, through dialogues between the novel, the BNCC, and the Law 10.639/03; to elaborate didactic sequences, in order to present the literary novel as a possibility for History classes. To achieve these goals, we will dialogue with authors Paul Ricouer (2007); Peter Lee (2006); Sandra Pesavento (2003) Nilma Lino Gomes (2012) and Rildo Cosson (2006). The proposal proposes to use the novel in order to promote debates on historical themes such as the enslavement of black people in Brazil, as well as racism in contemporaneity, encouraging interest and the habit of reading through a book that brings the influence of black authors who, despite their importance to Brazilian literature and historiography, are mostly unknown to students. The research presents as a product a Didactic Sequence with bridges between Literature and its possibilities for the teaching of History. The results show approachment of the students to the reading of the novel, allowing access and habit to other readings, as well as to develop the perception of their role as a subject of History, through the understanding of the emancipatory, humanizing, critical and transforming power existing in Literature and History.